ASEAN Multilateralism and the ARF prospects and challenges. [article]. - Quilop, Raymund Jose G.
In Southeast Asia, regional cooperation among the first six member of ASEAN has resulted to a brand of ASEAN multilateralism with its own unique characteristic features and principles. It is this brand of multilateralism that ASEAN now tries to export to the wider Asia-Pacific through the ARF. The author says that there is a need for the ARF to continue adapting to the changing regional environment, making necessary adjustments regarding the way it does things, in order to remain relevant and effective.
Keywords: Political Science-Periodicals.